Mycoflora Associated with Different Seed Sources of Pinus wallichiana - Joshi, Kirti; Harsh, N. S. K.; Rawat, P. S.; Shukla, A. N. (Indian Forester, 2004)
Seed samples from different sources of Pinus wallichiana from Himachal Pradesh and Uttaranchal were evaluated for the occurrence of seed mycoflora. A total of 13 fungi with 22 fungal species were isolated of which species of Aspergillus and Penicillium were dominant. Seed source Kufri (H.P.) reported maximum number of mycoflora i.e. 9 fungi, while in Sawat and Kharapathar (H.P.) only one fungus was recorded namely Aspergillus niger.